ChemInform Abstract: The State of Understanding of the Lithium‐Ion‐Battery Graphite Solid Electrolyte Interphase (SEI) and Its Relationship to Formation Cycling. Issue 28 (June 2016) - An, Seong Jin; Li, Jianlin; Daniel, Claus; Mohanty, Debasish; Nagpure, Shrikant; Wood, David L., III
Abstract: Review: in‐depth historical and current review; 261 refs.